“estrategias de intervención psicopedagógicas, en la disciplina, de los niños de tercer año de educación general básica de la escuela “Presidente Jaime Roldos” del cantón la troncal, provincia del cañar, durante el período académico, enero - septiembre del 2015”. - Lema Paredes, María Alexandra (2017)
The general objective of this work was to determine how the strategies of Psycho-pedagogic intervention improves the discipline of the students through the booklet entitled "My Good Behavior" which contains Strategies of Psycho-pedagogical Intervention; and was implemented in children of the third year of basic education at "Presidente Jaime Roídos" School in La Troncal Canton, Cañar province, during the academic period of January - September 2015 ", it was elaborated through didactic games, attention-concentration exercises and motivation exercises which improved the discipline of students, this research is justified by the importance of achieving comprehensive training of children therefore it took into account all aspects of the personality of students and it was not limited to provide only an intellectual education but was founded theoretically, it was elaborated consulting several authors based on the two variables of study which are the psych pedagogical strategies and the children' discipline, in a clear and adequate way. The population object of study were the students of the school where 37 children of them was considered as sample. An observation check list was used as a technique which was implemented in two moments before and after the booklet of psycho-pedagogical strategies. It allowed to collect the data to be tabulated and represented graphically in bars with their respective analyzes and interpretations. The research was designed as descriptive, explanatory and non- experimental, its type was correlational and field. The methods used were inductive, deductive and descriptive. The chi-square statistic was used in order to test both general and specific hypotheses, In this way, the respective conclusions were established, which determined that psycho-pedagogical intervention strategies improved students' discipline. Finally the necessary annexes are presented.